What's France got to do with it? Contemporary memoirs of Australians in France - de Nooy, Juliana (ANU Press, 2020)
While only one book-length memoir recounting the sojourn of an Australian in France was published in the 1990s, well over 40 have been published since 2000, overwhelmingly written by women. Although we might expect a focus on travel, intercultural adjustment and communication in these texts, this is the case only in a minority of accounts. More frequently, France serves as a backdrop to a project of self-renovation in which transplantation to another country is incidental, hence the question 'What's France got to do with it?' The book delves into what France represents in the various narratives, its role in the self-transformation, and the reasons for the seemingly insatiable demand among readers and publishers for these stories. It asks why these memoirs have gained such traction among Australian women at the dawn of the twenty-first century and what is at stake in the fascination with France.